Chiral Excitonic Organic Photodiodes for Direct Detection of Circular Polarized Light. (6th March 2019) - Schulz, Matthias; Balzer, Frank; Scheunemann, Dorothea; Arteaga, Oriol; Lützen, Arne; Meskers, Stefan C. J.; Schiek, Manuela
Abstract: A facile route to soft matter self‐powered bulk heterojunction photodiode detectors sensitive to the circular polarization state of light is shown based on the intrinsic excitonic circular dichroism of the photoactive layer blend. As light detecting materials, enantiopure semiconducting small molecular squaraine derivates of opposite handedness are employed. Via Mueller matrix ellipsometry, the circular dichroism is proven to be of H‐type excitonic nature and not originating from mesoscopic structural ordering. Within the green spectral range, the photodiodes convert circular polarized light into a handedness‐dependent photocurrent with a maximum dissymmetry factor of ±0.1 corresponding to 5% overall efficiency for the polarization discrimination under short circuit conditions. On the basis of transfer matrix optical simulations, it is rationalized that the optical dissymmetry fully translates into a photocurrent dissymmetry for ease of device design. Thereby, the photodiode's ability to efficiently distinguish between left and right circularly polarized light without the use of external optical elements and voltage bias is demonstrated. This allows a straightforward and sustainable future design of flexible, lightweight, and compact integrated platforms for chiroptical imaging and sensing. Abstract : Circular polarized light (CPL) detection is facilitated by strong excitonic circular dichroism of chiral small molecular semiconductors in a bulk heterojunction (BHJ) photodiode. The supramolecular exciton chirality is conserved in the BHJ blend allowing direct, CPL sensitive photovoltaic conversion without the need for additional polarization manipulating elements.